SYMBOLIZATION OF KERIS PAMOR IN THE MANIFESTATION OF SELF-IDENTITY IN THE SOKOSONGO KERIS COMMUNITY IN SEMARANG DISTRICT - Abram Wijaya, Stevanus; Riadi Syafutra Siregar; Septina Galih Pudyastuti (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Keris in the understanding of the Indonesian people, especially we as Javanese, understand the keris as a form of Tosan Aji. Javanese people adopt the meanings of the keris through prestige, using the keris as a means of increasing self-confidence and increasing a sense of enthusiasm or ethos in work. Research on the symbolization of prestige on the keris blade is to show the connection between the meaning of the symbol of prestige of the keris and the formation of a person's self-identity. These prestiges are divided into several elements that form them, namely, water, fire, air, earth and special prestige. The keris that will be discussed will be researched using qualitative methods and using an ethnographic approach. This research was carried out in Kesongo Hamlet, Tuntang District, Semarang Regency. In analyzing the data, ethnographic data analysis techniques will be used as an instrument in understanding cultural meaning which includes Domain Analysis, Taxonomic Analysis, Component Analysis and Cultural Theme Analysis. The symbolism in this keris, through its prestige, aims to be a means of prayer and also education or knowledge for its owner, but if the owner does not want to try and does not want to develop, then the prayers and hopes that exist will not come true.